Descriptive analysis of kinematics and kinetics of catchers throwing to second base from their knees. (August 2016) - Plummer, Hillary A.; Oliver, Gretchen D.
Abstract: In order to decrease the amount of time that it takes the catcher to throw the ball, a catcher may chose to throw from the knees. Upper extremity kinematics may play a significant role in the kinetics about the elbow observed in catchers throwing from the knees. If relationships between kinematics and kinetics exist then the development of training and coaching instruction may help in reduced upper extremity injury risk. Twenty-two baseball and softball catchers (14.36 ± 3.86 years; 165.11 ± 17.54 cm; 65.67 ± 20.60 kg) volunteered. The catchers exhibited a less trunk rotation (5.6 ± 16.2°), greater elbow flexion (87.9 ± 21.4°) and decreased humeral elevation (71.1 ± 12.3°) at the event of maximum shoulder external rotation as compared to what has previously reported in catchers. These variables are important, as they have previously been established as potential injury risk factors in pitchers, however it is not yet clear the role these variables play in catchers' risk of injury. A positive relationship between elbow varus torque during the deceleration phase and elbow flexion at MIR was observed ( r = 0.609; p = 0.003). Throwing from the knees reduces a catcher's ability to utilize the proximal kinetic chain and this may help to explain why their kinematics and kinetics differ from what has previously been presented in the literature.